Censo e ecologia comportamental de macaco prego - Cebus libidinosus - em área de cerrado do parque estadual Altamiro de Moura Pacheco, Goiânia-GO - Villar, Daniell Nunes Alves (2006)
Censuses of non-human primate populations play an important role in primatological field research, due to the increasing loss of natural habitats, particularly in the intertropical regions of the planet. The cerrado is the second largest Brazilian biome. It is basically located in the country´s central plateau, and has lost a great part of its original cover due to agricultural expansion. The capuchin monkeys of the cerrado region, Cebus libidinosus, were previously considered a subspecies of Cebus apella, but had their taxonomical status raised to that of species. The lack of data on this species is confirmed by a scarcity of studies that is not the case for other species of the genus. In this sense, the objectives of this study are the collection of data about the abundance, density, size and composition of groups, and habitat preference, represented by habitat type and height of support. Data were collected and analyzed, taking into consideration the seasonal aspects of the region. The study area is the Parque Estadual Altamiro de Moura Pacheco - PEAMP (16o 30' a 16o 34' S e 49o 07' a 49o 11' W), located in the southeastearn region of the state of Goiás, and occupying an area of approximately 3400 há. The climate is tropical hot and subhumid (Cwa), with two well defined stations, one dry and one humid. The altitude varies between 760 and 970m, and its main water stream is the Ribeirão João Leite. Systematic census data were collected from june and dezember of 2004, including therefore months within both the dry and the humid stations. The linear transect method was used, in which, besides the traditional census measures, data was also collected on the type of habitat, the height of utilized support, size and composition of observed groups were registered for 10 minutes after each groupo was located. A total of 374,7 km were walked, distributed in the two regions of PEAMP (North:: 189,18 km; South: 185,52 km). The abundance of capuchin monkeys was estimated in 1,79 groups for every 10 km, with rates varying between the dry and humid periods. The density varied between 3 and 6,7 groups per km2, depending on the method of analysis. Groups were preferentially observed in dry forests, and the prefered height varied from 6 and 10 m. The number of individuals observed varied from 1 to 15 individuals, with a significant difference between periods. (U= 303,5, p= 0,002). During the dry period, 94,87% of sightings were of 1 to 8 individuals, including 27,02 % of sightings of a single individual; during the wet season, 75% of sightings were of groups of 3 to 9 individuals. In general, the abundance of Cebus libidinosus was high, and its density was within those found for other species of the genus. These results are relevant, since the construction of a water dam will represent great impact not only to local primate communities, but of all faunistic biodiversity in the region. In this sense, the populational data hereby presented may aid in the elaboration and execution of a manegement plan for PEAMP.